2021
DOI: 10.17352/2455-5495.000037
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life in patients with end stage renal failure using KDQOL-SF

Abstract: Background: Chronic Renal Failure (CRF) is a general health problem having a genuine effect on the quality of life of the patients experiencing hemodialysis. Objectives: The aim and objectives of this cross-sectional study was to evaluate the effect of dialysis on the quality of life of patients with End Stage Renal Failure (ESRF). Methodology: Sample of 103 Patients Undergoing hemodialysis were included in study from two hospitals (public sector) of Quetta Pakistan. Information was gathered by the fruition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Baixos níveis de escolaridade, e o desempenho foram significativamente e independentemente associados com níveis baixos de QV no insuficiente renal crónico. Segundo Zahid et al (2021), no seu trabalho de pesquisa sobre a QV de doentes renais crónicos, verificou-se existir relação significativa com as variáveis: idade, ordenado mensal, situação conjugal e ocupação. Ficou patente, no referido estudo, que a insuficiência renal crónica afeta negativamente a qualidade da vida do doente, influenciando a sua saúde psicológica, capacidade física e, além disso, a vida pessoal, não se tendo obtido resultados significativos para a residência, o sexo e o estado de saúde.…”
Section: Enquadramentounclassified
“…Baixos níveis de escolaridade, e o desempenho foram significativamente e independentemente associados com níveis baixos de QV no insuficiente renal crónico. Segundo Zahid et al (2021), no seu trabalho de pesquisa sobre a QV de doentes renais crónicos, verificou-se existir relação significativa com as variáveis: idade, ordenado mensal, situação conjugal e ocupação. Ficou patente, no referido estudo, que a insuficiência renal crónica afeta negativamente a qualidade da vida do doente, influenciando a sua saúde psicológica, capacidade física e, além disso, a vida pessoal, não se tendo obtido resultados significativos para a residência, o sexo e o estado de saúde.…”
Section: Enquadramentounclassified
“…Another study in Pakistan showed that liquid and food restrictions caused much stress to hemodialysis patients. Many patients were bothered by excessive thirst due to liquid limitations, especially during hot weather [11]. Multiple national studies have been conducted utilizing the Kidney Disease Quality of Life-36 (KDQOL-36) questionnaire in Egypt and Saudi Arabia, and no studies have been conducted in Palestine utilizing this tool [12,13].…”
Section: Introductionmentioning
confidence: 99%